Dry season cattle grazing in the seasonally dry tropical forests of Costa Rica: importance in cattle ranching livelihoods and impacts on forest botanical composition and diversity - Godinot, Florent (2019)
Tesis (Mag. Sc.) -- CATIE, 2019